Shared Motifs among Neighbors: Small-Scale Objects, Hegemony, and Cultural Influence in the Late Bronze and Iron Age Levant - Thompson, Shane M. (Near Eastern archaeology, 2024)
This article examines the presence of small-scale objects (i.e., pottery, scarabs, seals, etc.) in the Late Bronze and Iron Age Levant as a means by which to measure the impact of foreign rule on the nonelites. It concludes that these objects are not useful to discussions of Assyrian, Egyptian, or Hittite hegemony, but rather that they are additional support for the interconnectivity of the Late Bronze and Iron Ages. In fact, these objects are expected to appear in the archaeological record of neighbors. This article, then, cautions against using material culture, especially small-scale material culture, as a means by which to draw large conclusions.